2002
DOI: 10.1046/j.0306-5251.2001.01546.x
|View full text |Cite
|
Sign up to set email alerts
|

Local nitric oxide release does not affect tachyphylaxis to angiotensin II in dorsal hand veins in man in the presence of prostaglandin synthesis inhibition

Abstract: Aims Local prostaglandin (PG) production contributes to tachyphylaxis to angiotensin II (ANGII) in veins. Our aim was to assess the hypothesis that local nitric oxide (NO) generation is also, in part, responsible for tachyphylaxis to ANGII in veins, using the Aellig dorsal hand vein technique. Methods Eight healthy male volunteers received 600 mg of aspirin (orally) to inhibit PG production. The venoconstrictor effects of ANGII and noradrenaline (NA) were then compared in dorsal hand veins during co-infusion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
1
2
1
Order By: Relevance
“…Moreover, in marked contrast to the stimulation observed when AII was administered alone, the enhanced response induced by the AII ϩ NE mixture showed no evidence of tachyphylaxis during six successive applications. A similar AII ϩ NE synergism has been reported in a number of other vascular preparations, including human coronary and digital arteries (9,10,30), with previous investigators also noting that the tachyphylaxis observed with AII alone was eliminated by co-application of NE with the AII (24,25). Our experiments with a selective AT 1 -type vascular-receptor antagonist demonstrated that this synergism between AII and NE in human gastroepiploic arteries is dependent on activation of the AT 1 -receptor subtype.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Moreover, in marked contrast to the stimulation observed when AII was administered alone, the enhanced response induced by the AII ϩ NE mixture showed no evidence of tachyphylaxis during six successive applications. A similar AII ϩ NE synergism has been reported in a number of other vascular preparations, including human coronary and digital arteries (9,10,30), with previous investigators also noting that the tachyphylaxis observed with AII alone was eliminated by co-application of NE with the AII (24,25). Our experiments with a selective AT 1 -type vascular-receptor antagonist demonstrated that this synergism between AII and NE in human gastroepiploic arteries is dependent on activation of the AT 1 -receptor subtype.…”
Section: Discussionsupporting
confidence: 55%
“…In our preparations, repeated exposure to AII led to a rapid fading of the induced contraction, whereas the VP-and NE-induced contractions remained more or less constant throughout the same exposure protocols. We cannot shed additional light on the mechanism underlying this AII tachyphylaxis, although our results confirm that this phenomenon is not dependent on endothelium-derived vasodilators such as nitric oxide (24). At present, it seems that AII tachyphylaxis may involve receptor desensitization, with decreased activation of phospholipase C (25).…”
Section: Discussioncontrasting
confidence: 36%
See 2 more Smart Citations